2019
DOI: 10.1007/s40501-019-00190-y
|View full text |Cite
|
Sign up to set email alerts
|

Digital Mental Health for Alcohol and Substance Use Disorders

Abstract: Purpose Only about 20% of people suffering from substance use disorders access available treatments due to various obstacles; digital interventions could potentially overcome some of these. Meta-analyses suggest the strongest evidence for interventions targeting alcohol use reduction, followed by cannabis and illicit substances. However, most randomized controlled trials (RCTs) used unguided standalone interventions compared to non-active controls, with limited follow-up periods and disregarded comorbidity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 58 publications
(58 reference statements)
5
31
0
Order By: Relevance
“…Electronic screening and brief intervention programs, which use mobile tools to screen for excessive alcohol use and deliver personalized feedback, have been found to effectively reduce alcohol consumption and alcohol-related problems [ 58 ]. However, rigorous evaluation trials of digital interventions targeting nonalcohol substance use are limited [ 7 ]. Furthermore, although a systematic review concluded that conversational agents showed preliminary efficacy in reducing psychological distress among adults with mental health concerns compared with inactive control conditions [ 27 ], this is the first published study of a conversational agent adapted for substance use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic screening and brief intervention programs, which use mobile tools to screen for excessive alcohol use and deliver personalized feedback, have been found to effectively reduce alcohol consumption and alcohol-related problems [ 58 ]. However, rigorous evaluation trials of digital interventions targeting nonalcohol substance use are limited [ 7 ]. Furthermore, although a systematic review concluded that conversational agents showed preliminary efficacy in reducing psychological distress among adults with mental health concerns compared with inactive control conditions [ 27 ], this is the first published study of a conversational agent adapted for substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Web-based interventions and digital health apps may reduce or eliminate common, significant barriers to traditional SUD treatment (eg, stigma; financial, time, and transportation constraints; lack of access to qualified providers; challenges navigating complex treatment systems; and low perceived utility) [ 6 ]. Preliminary evidence suggests that digital SUD interventions affect substance use behavior [ 6 , 7 ] and have the potential to reduce the population burden of SUDs. To date, most digital SUD interventions have been delivered on a web platform, rather than via mobile apps.…”
Section: Introductionmentioning
confidence: 99%
“…The identified lack of empirical evaluation of the proposed solutions was reflected in the findings of a meta-analysis on digital interventions for alcohol and substance use disorders, reporting limitations in the number of randomized control trials (RCTs) in that area [ 117 ]. Another review on RCTs on the effectiveness of occupational e-mental health concluded the need for more detailed and specific effectiveness research [ 246 ].…”
Section: Discussionmentioning
confidence: 99%
“…Digital health applications (apps) can reduce barriers to traditional SUD treatment including stigma, costs and inadequate insurance coverage, time demands, transportation needs, lack of access to qualified providers, and challenges navigating complex treatment systems ( Giroux et al, 2017 ). Preliminary evidence suggests that digital SUD interventions can reduce substance misuse ( Boumparis et al, 2019 ; Giroux et al, 2017 ). Scalable digital SUD interventions could lessen the population-level burden of SUDs.…”
Section: Introductionmentioning
confidence: 99%